2021
DOI: 10.3934/agrfood.2021055
|View full text |Cite
|
Sign up to set email alerts
|

Study on antioxidant activity of crude peanut oils and refined cottonseed oils from Burkina Faso

Abstract: <abstract> <p>Vegetable oils are among the foodstuffs produced and consumed in abundance by the population in Burkina Faso. These edible oils are nutrient sources for health. However, the oxidation of edible oils is a phenomenon that leads to their degradation. Hence, the objectives of this study were to determine the antioxidants compounds, to evaluate the antioxidant activity of vegetable oils produced in Burkina Faso and to propose good manufacturing practices. Thus, 32 samples of crude peanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…After 10 d storage at refrigerated temperature (Figure 4b), the inhibition effect of whey protein-based edible film on bacterial growth was high compared to 25°C storage temperature. Zio et al (2021) concluded that the incorporation of essential oil with high phenolic compounds and antioxidant substances on the edible film caused antimicrobial, lipid-lowering, anticarcinogenic, and anti-inflammatory effects of edible film. Therefore, higher concentration of PO was proven to exert significant effect in extending chicken meat shelf life.…”
Section: Effect Of Edible Film On Chicken Meat Bacterial Loadmentioning
confidence: 99%
“…After 10 d storage at refrigerated temperature (Figure 4b), the inhibition effect of whey protein-based edible film on bacterial growth was high compared to 25°C storage temperature. Zio et al (2021) concluded that the incorporation of essential oil with high phenolic compounds and antioxidant substances on the edible film caused antimicrobial, lipid-lowering, anticarcinogenic, and anti-inflammatory effects of edible film. Therefore, higher concentration of PO was proven to exert significant effect in extending chicken meat shelf life.…”
Section: Effect Of Edible Film On Chicken Meat Bacterial Loadmentioning
confidence: 99%
“…It contains antioxidants and exhibits anti‐inflammatory, anticancer, and anti‐allergic effects on humans (Sharif et al, 2019). Approximately 50% of CSO is consumed as cooking oil, 36% for baking and frying, and the remainder as margarine (Zio et al, 2021). CSO has higher saturated fatty acid content than other vegetable oils and is beneficial for human consumption.…”
Section: Uses Of Cottonseedmentioning
confidence: 99%
“…According to Rodrigues et al (2011), peanut oil is used in the production of margarines, surfactants, medicines, and cosmetics. From peanut oil's biological activities, including its ability to repress the bacteria growth such as Staphylococcus aureus, Listeria ivanovii, L. innocua, Bacillus cereus, Enterococcus hirae, and Pseudomonas aeruginosa (Sebei et al 2013), antioxidant potential resulting from its great content of total phenolic compounds (Matthäus and Özcan 2015;Zio et al 2021), and anti-aging due to γtocopherol, vitamin E, α-tocopherol and phytosterols (Matthäus et al 2015).…”
Section: Introductionmentioning
confidence: 99%